A study of clinical profile and quality of life in patients with scabies - R., Bindushree; Hosthota, Abhineetha (International Journal of Research in Dermatology, 2021)
Background: Scabies is an ectoparasitic dermatosis caused by Sarcoptes scabiei and is a public health issue in all countries regardless of socioeconomic status. Scabies can lead to stigmatization, depression, insomnia, and may significantly affect the quality of life. The aim of the study was to find the demographic profile, clinical morphology and quality of life in patients suffering from scabies. Methods: This was a prospective, non-interventional, hospital-based cross-sectional study. Adult patients with scabies reporting to the dermatology department were enrolled in the study. Demographic details, clinical findings, past history and family history was recorded in a proforma. Questionnaire about quality of life was given to the patients and a detailed analysis was done. Results: A total of 120 cases of scabies were enrolled in this clinical study. The most affected age group was between 18 and 30 years. Most common site involved was interdigital spaces (83%) followed by genitalia (48%) and abdomen (42%). The most common lesion was excoriation (91%) followed by papule (88%) and nodules (33%). Out of 120 patients, 111(92%) patients experienced difficulty in working at the work place, 83.3% of patients had feeling of embarrassment, social relationship was affected in 82.5% of patients. Majority of the patients (38.5%) had mild impairment of quality of life. Conclusions: Feeling of embarrassment, difficulty in work place, social stigmata and depression were frequently observed in patients with scabies. In our study scabies mildly affected the quality of life.